PENGEMBANGAN APLIKASI WEB KOMIK STRIP UNTUK MENINGKATKAN PEMAHAMAN SISWA TERHADAP TEKS ANEKDOT DENGAN MUATAN EKOKRITIK - Septiani, Suci; Shofi, Moh. Shofiuddin (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2024)
This study aims to develop a comic strip web application media that can improve students' understanding of anecdotal text with ecocritical content. The development was conducted using the 3D model (Define, Design, Develop) which includes needs analysis, design, and product development. The feasibility test involved media, language, and material experts, while the practicality test was conducted by teachers and students. The validation results show that this media is feasible to use with a percentage of 82.5% from media experts, 93% from language experts, and 94% from material experts. The practicality test resulted in 98% from teachers and 83% from students, indicating that this application is practical to use in learning. As the results, this comic strip media not only facilitates students' understanding of anecdote texts, but also instills environmental awareness through ecocritical content delivered interactively. Keywords: web application, ecocriticism, anecdote text